SPARC, a Novel Regulator of Vascular Cell Function in Pulmonary Hypertension. Issue 12 (17th February 2022) - Veith, Christine; Vartürk-Özcan, Ipek; Wujak, Magdalena; Hadzic, Stefan; Wu, Cheng-Yu; Knoepp, Fenja; Kraut, Simone; Petrovic, Aleksandar; Gredic, Marija; Pak, Oleg; Brosien, Monika; Heimbrodt, Marie; et al.
Abstract : Background: Pulmonary hypertension (PH) is a life-threatening disease, characterized by excessive pulmonary vascular remodeling, leading to elevated pulmonary arterial pressure and right heart hypertrophy. PH can be caused by chronic hypoxia, leading to hyper-proliferation of pulmonary arterial smooth muscle cells (PASMCs) and apoptosis-resistant pulmonary microvascular endothelial cells (PMVECs). On reexposure to normoxia, chronic hypoxia-induced PH in mice is reversible. In this study, the authors aim to identify novel candidate genes involved in pulmonary vascular remodeling specifically in the pulmonary vasculature. Methods: After microarray analysis, the authors assessed the role of SPARC (secreted protein acidic and rich in cysteine) in PH using lung tissue from idiopathic pulmonary arterial hypertension (IPAH) patients, as well as from chronically hypoxic mice. In vitro studies were conducted in primary human PASMCs and PMVECs. In vivo function of SPARC was proven in chronic hypoxia-induced PH in mice by using an adeno-associated virus–mediated Sparc knockdown approach. Results: C57BL/6J mice were exposed to normoxia, chronic hypoxia, or chronic hypoxia with subsequent reexposure to normoxia for different time points. Microarray analysis of the pulmonary vascular compartment after laser microdissection identified Sparc as one of the genes downregulated at all reoxygenation time points investigated. Intriguingly, SPARC was vice versa upregulated in lungs during development of hypoxia-induced PH in mice as well as in IPAH, although SPARC plasma levels were not elevated in PH. TGF-β1 (transforming growth factor β1) or HIF2A (hypoxia-inducible factor 2A) signaling pathways induced SPARC expression in human PASMCs. In loss of function studies, SPARC silencing enhanced apoptosis and reduced proliferation. In gain of function studies, elevated SPARC levels induced PASMCs, but not PMVECs, proliferation. Coculture and conditioned medium experiments revealed that PMVECs-secreted SPARC acts as a paracrine factor triggering PASMCs proliferation. Contrary to the authors' expectations, in vivo congenital Sparc knockout mice were not protected from hypoxia-induced PH, most probably because of counter-regulatory proproliferative signaling. However, adeno-associated virus–mediated Sparc knockdown in adult mice significantly improved hemodynamic and cardiac function in PH mice. Conclusions: This study provides evidence for the involvement of SPARC in the pathogenesis of human PH and chronic hypoxia-induced PH in mice, most likely by affecting vascular cell function.